Efeito de intervenção nutricional sobre a percepção e o consumo de frutas e hortaliças - Maria Cecília Ramos de Carvalho (2019)
This study aims to describe the effect of misperceived fruit and vegetable (FV) intake on evolution of stages of change for eating FV and estimated FV intake in adults and seniors. A randomized controlled community trial was carried out with a representative sample of Health Academy Program users in Belo Horizonte, Brazil, comprised of 3414 service users. Perception of intake adequacy was measured by the Transtheoretical Model (TTM) Stages of Change and FV intake was estimated from brief validated questions, both at baseline and after intervention. Participants whose perception of intake adequacy matched estimated intake maintained their original classification in one of the five original stages (pre-contemplation, contemplation, preparation, action or maintenance). Users with low FV intake who believed it was adequate were classified as pseudomaintenance (PM); those who met guidelines without recognizing it were classified as non-reflective action (NRA). Afterwards, perception was dichotomized in “concordant (one of the five original stages)” or “discordant (PM or NRA)”. Participants were randomized to control or intervention group and TTM-based tailored intervention was performed in the intervention group by trained dietitians and psychologists for seven months, while the control group received usual care (physical activity three times a week and group health education not including FV intake interventions). The pedagogy of Paulo Freire was also used as a theoretical framework for the intervention. Participants were mostly women of middle age, with low schooling, low FV intake and misperceived intake of fruit (31.1%) and vegetables (51.9%). Users with misperceived intake at baseline had lower odds of regressing to lower stages [adjusted odds ratios: fruit 0,47 (0,36-0,60); vegetables 0,17 (0,13-0,22)] and also lower odds of progressing to higher stages after intervention [adjusted odds ratios: fruit 0,06 (0,04-0,09); vegetables 0,01 (0,01-0,02)]. Fruit intake increased in both categories of perception in the intervention group, but change in the misperception category was larger than in the concordant perception category (0.5±1.3 versus 0.2±1.3 servings). Individuals with misperceived intake also increased vegetables intake (0.1±1.4 servings) while those with concordant perception decreased it (-0.6±1.7). Baseline self-efficacy and decisional balance did not predict changes in FV intake among the discordant perception group. We conclude that that discordant Efeito de intervenção nutricional sobre a percepção e o consumo de frutas e hortaliças 12 perception affects stage evolution in two different directions, reducing the odds of stage progression and regression. Despite the higher increases in FV intake among discordant perception individuals, change was still small. This may indicate the need to improve participants’ awareness of their stage, FV intake and their personal motivations to increase or maintain it. Hence, there is a need to employ the stage reclassification in PM or NRA before intervention begins.